Microbiological and physical chemical evaluation of traditional cream cheese brands with different market value (Research, Society and Development, 2020)
The objective of this study was to evaluate the physical-chemical and microbiological characteristics of four brands of traditional cream cheeses with different market value. Three batches of the four commercial brands of cream chesses were acquired, totaling 12 samples. The differences in pH, titratable acidity, starch, fat in dry extract, moisture, ash, lipids, protein, and carbohydrates were measured by physico-chemical analyzes, while the of thermotolerant coliforms and Staphylococcus aureus spp. counts were performed by microbiological analyzes. Regarding the four evaluated brands, < 3 Most Probable Number of thermotolerant coliforms and an absence of colonies characteristic of Staphylococcus aureus were found. There was no significant difference between the brands studied at 5% of significance for the fat in dry extract, moisture, ash and lipids. All the analyzed cream cheese samples differed significantly (p < 0.05) for the starch content. The analyzed samples showed satisfactory hygienic-sanitary quality. The physical-chemical evaluation results presented standardization in the cream cheese preparation, regardless of the amount charged, however, there was a lack of information on the use of starch on all labels.